Penggunaan Material Komposit Berbahan Dasar Serat Batang Tembakau dan Serat Batang Tumbuhan Kenaf dalam Meredam Kebisingan - Andriansyah Nurauf; Okik Hendriyanto Cahyonugroho (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Natural fiber reinforced composites are widely applied to equipment with materials that have a combination of two basic properties, namely strength and lightness. This study aims to determine the optimum ability of kenaf stem fiber and tobacco stem fiber which contain relatively high cellulose to be used as soundproofing materials and also to utilize tobacco stems which were originally considered as agricultural waste to become a more useful raw material. Comparison of stem fiber ratio kenaf and tobacco stem fiber 100:0, 60:40, 50:50, 40:60, and 0:100. From the research results obtained, the composite exhaust produces the smallest sound, namely 81.6 dBA at a fiber ratio variation of 60:40 at 1500 RPM and produces the biggest sound, namely 99.1 dBA at a fiber ratio variation of 0:100 at RPM 3500. Results it can be said that the damping of the composite exhaust is quite good because it is not too far from the quality standard threshold of 83 dBA. The ability of kenaf stem fiber to reduce noise is better than that of tobacco stem fiber because the cellulose content in kenaf stem fiber (by 50%) is higher than that of tobacco stem fiber (by 37%).